Internal problems of development aid - Karl Wolfgang Menck (Intereconomics, 1977)
The unsolved internal problems of Germany's development aid require an early reexamination of the objectives and the concept of development aid against the quickly shifting world-economic background. Numerous hitherto unsettled questions concerning technical aid and its implementation have to be answered soon and expertly.
Keywords: 330; Development Policy